Effects of Different Arm Immobilization Methods on Set-Up Accuracy in Photon and Proton Radiotherapy Techniques for Breast Cancer: A Systematic Review - Hadisinia, Tahereh; Abbaspour, Samira; Abedi-Firouzjah, Razzagh (Archive of Oncology, 2025)
Purpose: This study aimed to review the effects of different arm immobilization methods on set-up accuracy in photon and proton radiotherapy techniques for breast cancer with supraclavicular lymph node (LN) involvement. Methods: A systematic review was conducted using a comprehensive literature search of English-language sources from PubMed, Google Scholar, ScienceDirect, and Medline databases, with no restrictions on publication date. Two independent reviewers assessed and screened titles and abstracts for inclusion. Results: Following screening and eligibility determination, 14 articles were included. Of these, 11 studies focused on photon radiotherapy (8 in the supine position and 3 in the prone position), while 3 studies examined proton radiotherapy. Conclusion: For the supine position, the "both hands above the head" method demonstrated superior set-up accuracy. In the prone position, the crawl position combined with the deep inspiration breath-hold (DIBH) method outperformed other approaches. In proton radiotherapy for breast cancer, both "hands-up" and "hands-down" methods yielded equivalent results.